Effect Of Draw Bead Geometry And Applied Force To Drawing Of Aluminium AA6061 - Lo, Thye Wei Clarence (Universiti Sains Malaysia, 2019)
In this thesis, the effect of draw bead radius and draw bead apply force are being investigated. The effect are being study and compare by measuring the restraining force generated by draw bead under different setting of draw bead radius and apply force. The material selected as specimen are aluminium AA6061. A specific draw bead with exchangeable male draw bead and a test jig with force apply mechanism are being design and fabricated. The test jig and draw bead are then being install on Universal Testing Machine (UTM) to perform the experiment. The UTM function to perform pulling of specimen through draw bead and measure the restraining force generated by draw bead during the pulling operation. Three different draw bead radius (5mm, 6mm and 7mm) and three different torque are being apply to force apply mechanism to produce three different force for testing. The results shows that as higher force being apply to draw bead, higher restraining force will be generated. While 6mm draw bead radius will generate highest restraining force and any further increase or decrease in radius will decrease restraining force generated. Results also shows that high possibility of specimen fracture at setting of 5mm radius 4.5Nm torque and 6mm radius 4.5Nm torque.